Decadal to monthly timescales of magma transfer and reservoir growth at a caldera volcano - Costa, Fidel (2012)
Caldera-forming volcanic eruptions are low-frequency, high impact events capable of discharging tens to thousands of cubic kilometres of magma explosively on timescales of hours to days, with devastating effects on local and global scales1. Because no such eruption has been monitored during its long build-up phase, the precursor phenomena are not well understood. Geophysical signals obtained during recent episodes of unrest at calderas such as Yellowstone, USA, and Campi Flegrei, Italy, are difficult to interpret, and the conditions necessary for large eruptions are poorly constrained. Here we present a study of pre-eruptive magmatic processes and their timescales using chemically zoned crystals from the ‘Minoan’ caldera-forming eruption of Santorini volcano,Greece, which occurred in the late 1600s BC. The results provide insights into how rapidly large silicic systems may pass from a quiescent state to one on the edge of eruption. Despite the large volume of erupted magma (40–60 cubic kilometres), and the 18,000-year gestation period between the Minoan eruption and the previous major eruption, most crystals in the Minoan magma record processes that occurred less than about 100 years before the eruption. Recharge of the magma reservoir by large volumes of silicic magma (and some mafic magma) occurred during the century before eruption, and mixing between different silicic magma batches was still taking place during the final months. Final assembly of large silicic magma reservoirs may occur on timescales that are geologically very short by comparison with the preceding repose period, with major growth phases immediately before eruption. These observations have implications for the monitoring of long-dormant, but potentially active, caldera systems.